The past can't heal us : the dangers of mandating memory in the name of human rights / Lea David. - David, Lea, 1976- (Human rights in history., 2020)
In this innovative study, Lea David critically investigates the relationship between human rights and memory, suggesting that, instead of understanding human rights in a normative fashion, human rights should be treated as an ideology. Conceptualizing human rights as an ideology gives us useful theoretical and methodological tools to recognize the real impact human rights has on the ground. David traces the rise of the global phenomenon that is the human rights memorialization agenda, termed 'Moral Remembrance', and explores what happens once this agenda becomes implemented. Based on evidence from the Western Balkans and Israel/Palestine, she argues that the human rights memorialization agenda does not lead to a better appreciation of human rights but, contrary to what would be expected, it merely serves to strengthen national sentiments, divisions and animosities along ethnic lines, and leads to the new forms of societal inequalities that are closely connected to different forms of corruptions.